Analisis Kontribusi Pajak Parkir Terhadap Peningkatan Pendapatan Asli Daerah Pada Otoritas Pengelola Pajak Dan Retribusi Daerah Kota Probolinggo - Riska Wulandari; Agus Wahyudi; Endah Puspita Sari (Aafiyah: Jurnal Multidisiplin Ilmu, 2024)
This research is about the parking tax burden in Probolinggo City. The aim of this research is to determine the contribution of parking tax to local revenue in Probolinggo City. This research was analyzed using quantitative descriptive methods. The survey was conducted at the Probolinggo City Regional Tax Assessment Administration Office. Based on research results, receipts from parking tax donations in Probolinggo City reached IDR 3,862.05 billion in 2018, reaching IDR 4,083.6 million in 2019 and IDR 4,083.6 million in 2020. 4,158.7 million. Based on the analysis of the contribution level of parking tax revenue in the City of Probolinggo, it can be said to be able to make a full contribution to increasing the local revenue of the City of Probolinggo. In 2018 the percentage was 105.24%. The percentage in 2019 was 111.18%, and the highest percentage in 2020 was 115.22%. This is because the services of the Probolinggo City Government are being utilized optimally in exploring possible parking rates.